Analisis Deskriptif Strategi Self-Regulated Learning Pada Pelajar Dengan Internet Gaming Disorder: Descriptive Analysis of Self-Regulated Learning Strategies in Students with Internet Gaming Disorder - Anwarul kirom Anwar; Nurus Sa'adah; Al Furqon; Wike Silfia (UIN Kiai Haji Achmad Siddiq Jember, 2023)
This study aims to determine self-regulated learning strategies for students with internet gaming disorder. By using the literature review method. With literature sources obtained from the google-scholar database on self-regulated learning and internet gaming disorder, it is then studied in depth and draws a conclusion for this study. This study found that the application of self-regulated learning strategies to students with internet gaming disorder could be based on self-regulation of the students themselves.